From Overwhelm to Success: Empowering Educational Personnel with Microlearning and Self-Paced Training to Maximize Performance and Avoid Burnout - Moses Adeleke Adeoye; Entika Fani Prastikawati; Rasheedat Modupe Oladimeji; Adeseko Sunday Olaifa (Unib Press, 2024)
This study investigates how self-paced training and microlearning can empower teachers, improve their output, and keep them from burning out. The heavy workloads and high levels of stress that teachers and administrators, commonly experience can negatively impact their general well-being and capacity to perform their professions efficiently. This study explores the possibility of self-paced training and microlearning as tools to empower educational personnel to solve these issues. The distribution of brief, bite-sized learning modules that concentrate on particular subjects or abilities is referred to as microlearning. Due to the modules' quick completion times and ease of access, educators can accommodate learning into their already hectic schedules. Self-paced training gives people the freedom to learn at their own pace and customizes and adapts their learning process. Through the use of self-paced training and microlearning, educational staff members can acquire critical knowledge and skills in a convenient and customized way. Furthermore, by enabling educators to prioritize their professional growth and manage their workload, these training methods can assist in avoiding burnout in the classroom. The study will also investigate the possible obstacles and difficulties that educators may encounter while introducing microlearning and self-paced training. To sum up, self-paced training and microlearning have the power to completely change how educators acquire knowledge and grow as professionals. Teachers can enhance their performance, knowledge, and skills by implementing these tactics, which will help students and the educational system as a whole.